Bi-directional associations between child fussy eating and parents’ pressure to eat: who influences whom? - Jansen, Pauline W (Physiol Behav, 2017)
BACKGROUND: Fussy eating is common in young children, often raising concerns among parents. The use of pressuring feeding practices may provoke or worsen child fussiness, but these practices could equally be a parent’s response to child fussy eating. OBJECTIVE: In longitudinal analyses, we assessed directionality in the relation between fussy eating and parent’s pressure to eat across childhood. METHODS: Study participants were 4845 mother-child dyads from the population-based Generation R cohort in the Netherlands. The Child Behavior Checklist was used to assess fussy eating (2 items) at child ages 1½, 3 and 6 years. Parents’ pressure to eat was assessed with the Child Feeding Questionnaire (4 items) when children were 4 years old. All scale scores were standardized. RESULTS: Linear regression analyses indicated that preschoolers’ fussy eating prospectively predicted higher levels of parents’ pressure to eat at child age 4 years, independently of confounders (adjusted B=0.24, 95% CI: 0.21, 0.27). Pressure to eat at 4 years also predicted more fussiness in children at age 6 years, independently of confounders and of fussy eating at baseline (adjusted B=0.14, 95% CI: 0.11, 0.17). Path analyses indicated that the relation from fussy eating at 3 years to parenting one year later was stronger than from pressure at 4 years to fussy eating two years later (p<0.001). CONCLUSIONS: Our findings suggest bi-directional associations with parental pressuring feeding strategies being developed in response to children’s food avoidant behaviors, but also seemingly having a counterproductive effect on fussiness. Thus, the use of pressure to eat should be reconsidered, while providing parents alternative techniques to deal with their child’s fussy eating.